2010
DOI: 10.21061/jcte.v25i2.480
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Construction Teachers Engaged in Missouri’s Secondary School System

Abstract: The purpose of this study was to investigate the reasons construction teachers in the CTE field left the teaching profession in their first five years of service. The study also sought to determine if there was a significant difference in the retention rate of two-year alternatively certified teachers and four-year teaching degreed teachers and if there was a significant difference in why two-year certified and four-year teaching degreed teachers had considered leaving the profession. This was done through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Also of concern is the loss of teachers who are already in the classroom. McCandless and Sauer (2010) reported that many alternatively certified instructors feel that they lack the administrative support to succeed in the classroom. Research continues to show that teacher retention can be drastically improved with mentorship and induction programs.…”
Section: Resultsmentioning
confidence: 99%
“…Also of concern is the loss of teachers who are already in the classroom. McCandless and Sauer (2010) reported that many alternatively certified instructors feel that they lack the administrative support to succeed in the classroom. Research continues to show that teacher retention can be drastically improved with mentorship and induction programs.…”
Section: Resultsmentioning
confidence: 99%
“…As for studies that specifically pertain to the CTE environment, one noteworthy study was found on teacher retention in general (Vagi, Pivovarova & Miedel, 2019), and the retention of CTE teachers in specifically (Song, Martens, McCharen, & Ausburn, 2011). Another study was located on technical education teachers (Steinke & Putnam, 2007), one on business education teachers (Gaytan, 2008), one on construction teachers (McCandless & Sauer, 2010), and one study was located on consumer science teachers (Dainty, Sandford, Su, & Belcher, 2011).…”
Section: New Cte Job Turnovermentioning
confidence: 99%
“…In the survey conducted during that particular research, fully 86% (n = 146) of the respondents were convinced that poor working conditions negatively impacted the retention rate of business education teachers. In a study that took a close look at the reasons why new construction teachers left the education profession, conducted from the points of view of both stayers and leavers (McCandless & Sauer, 2010), it was seen that pay scale, although perceived to be important, was not nearly as much a factor in deciding to leave as was student discipline problems and poor administrative supervisory styles.…”
Section: Three Main Reasons For Stayingmentioning
confidence: 99%
“…Induction programs can address problems, contribute to teacher success, and encourage teachers to stay in the profession (Moir & Glass, 2001;Nesbitt & Mundt, 1993). Many educational institutions have implemented induction programs to help early career teachers become more successful in the teaching profession (McCandless & Sauer, 2010). In agricultural education, Franklin and Molina (2012) found more than 65% of American Association for Agricultural Education (AAAE)affiliated, teacher-preparation institutions provided beginning teacher assistance at some level.…”
mentioning
confidence: 99%